Trening vzdržljivosti pri kolesarjih - Ferlež, Mitja (Šport (Ljubljana), 2010)
The most recent studies have led to the finding that a bigger delivery of oxygen in the body during sport exercise improves a cyclist's performance in terms of endurance. The logical consequence of this finding is the question of how to increase the delivery of oxygen into the athlete's body during sport exercise and how to achieve this in the process of chronic endurance training.
Keywords: kolesarstvo; poraba kisika; trening; vzdržljivost